DEI as a Practice of Assembling: Translation and Transformation - Patel, Chandani (Radical Teacher, 2025)
As much as DEI work requires an aspiration towards futures free of oppression, ones that are more just and equitable, critical DEI carries within it the tension of the status quo and the possibility of liberation. Utilizing la paperson’s conceptualization of the scyborg –as a concept that identifies the messiness of agitating towards change within a system that is designed to maintain the status quo –I describe what critical DEI looks like within a tuition-charging preK-12 institution. I begin with describing a DEI from below from my location within a local landscape where DEI wars are waged in the classroom. I then discuss the strategies and conditions through which I labor, against front and backlash, and also against capitalism in its many insidious forms, as an act of self-preservation. And finally, I examine why I stay in this work and return to it over and over again through a sense of shared purpose and radical love. This is a correction to the original article. For information about the changes made, please see the erratum linked as a supplemental file on the article’s landing page. The information will also be available at https://radicalteacher.library.pitt.edu/ojs/radicalteacher/article/view/1395 in issue 132.